A study of dynamics of marine circuit breakers based on vibration. Issue 1 (1st February 2022) - Sun, Tao; Yang, Lian; Shu, Peng
Abstract: Marine circuit breaker is an important equipment on board, its mechanical failure generated by the vibration can cause the power system failure. Therefore, it is necessary to evaluate the structure of the circuit breaker system. The finite element method is used to establish the dynamics model of the whole circuit breaker system under the vibration, and the dynamic response analysis of the circuit breaker is carried out with real vibration load. According to the analysis results, the overall structural strength of the circuit breaker and the occurrence of mis-operation are evaluated, then the sensitive weak position of the circuit breaker structure are identified, and finally the structural optimization design is carried out.